Muslim Influencers and Moral Responsibility: An Ethical Analysis of Preaching on Digital Platforms - Najamudin Najamudin; Dwi Muliati; Amelia Agustin; Mansur Tenis (JISEI: Journal of Islamic Studies and Educational Innovation, 2026)
The development of digital media has given rise to a new phenomenon in dawah, namely the emergence of Muslim Influencers. This study aims to analyze the moral and ethical responsibilities of dawah that should be upheld by Muslim Influencers on digital platforms. The method used is qualitative with a library research approach, with data collected from various literature sources such as journals, books, and related academic works. The results of the study indicate that although the term "influencer" is not explicitly found in the Qur'an, its concept and responsibilities are implicitly reflected in QS. An-Nahl [16]: 125. Their presence has a significant influence on the mindset and behavior of society. However, dawah on social media also faces various challenges, such as inconsistent content, inadequate competence of preachers, and the risk of spreading unverified information. Therefore, this study concludes that The application of da'wah ethical values is very crucial. The main values that must be held include Sincerity and Truth (Sidiq), Patience, and Debate Ethics which are based on sincere intentions, clear goals, and the spirit of brotherhood in order to create a positive impact on the digital society.